1964
DOI: 10.1136/bmj.2.5404.280
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Carriers of Staphylococci

Abstract: A vital problem regarding hospital infection is to differentiate between dangerous and non-dangerous carriers.It is accepted that persons with septic lesions are more "dangerous " than healthy carriers. It Altogether 13% were positive in the perineum, 34% in the nose, and 31 % in the throat.The frequency of staphylococci isolated from single and multiple sites is illustrated in Table I. Perineal carriage was relatively seldom an isolated phenomenon-occurring in only 2.6 % in this series. Most often it was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Association between S. aureus nasal colonization and increased risk for infection was reported in the 1930s [44], and supported by several more recent studies [4, 12, 20, 44, 45]. It is suggested that S. aureus infections originate from endogenous nasal bacteria that are spread to the skin, which in turn cause infection when the integrity of the skin is compromised [20].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Association between S. aureus nasal colonization and increased risk for infection was reported in the 1930s [44], and supported by several more recent studies [4, 12, 20, 44, 45]. It is suggested that S. aureus infections originate from endogenous nasal bacteria that are spread to the skin, which in turn cause infection when the integrity of the skin is compromised [20].…”
Section: Introductionmentioning
confidence: 81%
“…The most frequent sites of colonization are considered to be the skin, the perineum and the pharynx [44]. Several authors stress the need for more studies, and suggest multi-body site sampling [9, 21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain typing suggested involvement of the same strains for both colonization sites [14]. Vice versa, about 50-70% of perineal carriers were also nasal carriers of the same strain [15]. It was reported that of 50 healthy male students screened, 11 (22%) had perineal carriage of S. aureus and that 5 of these were non-nasal carriers (10%) [16].…”
Section: Intestinal Carriage Frequencies Of S Aureus In Adultsmentioning
confidence: 99%
“…Second, misclassification of the exposure of main interest (MRSA colonization) was also a concern in this study. The baseline screening of MRSA colonization (sampling of nares and perineum) is estimated to have a sensitivity of approximately 80% to 95%, 18 resulting in 5% to 20% of undetected colonized patients at enrollment in the study. Moreover, during follow-up, some MRSA carriers probably became negative, whereas new colonization occurred and remained undetected in others.…”
Section: Discussionmentioning
confidence: 99%